Progress in surgical interventions for aortic root aneurysms and dissections. (2nd January 2022) - Parameswaran, Shamini; Ziganshin, Bulat A.; Zafar, Mohammad; Elefteriades, John A.
ABSTRACT: Introduction: The aortic root is a uniquely sensitive region as it anatomically encompasses the aortic valve leaflets and gives origin to the coronary arteries. These associated structures, in addition to the aortic tube, itself, add immensely to the complexity of replacing this segment when it is aneurysmal or dissected. Given this complexity, many contemporary choices for treatment of aortic root aneurysms have evolved over the past few decades. Areas covered: The aim of this study was to provide an updated review of the literature regarding various surgical options for management of aortic root aneurysmal disease. A systematic search in PubMed database was performed for articles related to various aortic root surgeries and outcomes published between 1998 and 2020. Expert opinion: For multiple technical options in aortic root replacement surgery, decades of surgical investigation and development have shown favorable results, which provide a formidable armamentarium to be used at the discretion of the surgeon to suit various patient anatomic patterns and risk profiles – while still durably controlling the aortic pathology and protecting from recurrence, valve dysfunction, progressive dilatation, and aortic dissection.